Professional Development and Lifelong Learning Opportunities for Library & Information Science Professionals through E-learning Portals / S.C. Kumaresan - S.C., Kumaresan (2011)
The objective of this paper is to sensitize professional associations, policy makers of various governments, university authorities and Library and Information Science (LIS) professionals at large, on the need to create a professional development program and a lifelong learning opportunity through e-learning portals especially in the developing countries. It also tries to explain the need for such an opportunity for learning, at a pace and time that is convenient to the learners. It portrays the probable role of professional associations, universities and government departments in fostering a rich and productive online learning environment and also tries to give a perspective of the LIS professionals who migrate to different parts of the world or within their country to work and the need for them to learn and develop professionally. This paper is an empirical study of the professional development needs and the difficulties in getting one by an expatriate Indian author who took up a job in the Middle East. It is inspired by the ―online learning‖ activities of professional associations such as the American Library Association (ALA) and the American Society for Information Science & Technology (ASIS&T). An attempt is made to identify professional development programs that can be rendered & accessed through e-learning portals and also attempts to suggest a model design for the delivery of Professional Development by all the stake holders. The learning outcome of this paper would be a strong understanding of the need to develop an online professional development program through e-learning portals by various LIS schools, professional associations and authorities from the education departments of different countries especially the developing countries.